Facet-mediated interaction between humic acid and TiO2 nanoparticles: implications for aggregation and stability kinetics in aquatic environments. Issue 6 (10th May 2019) - Zhang, Hui; Wang, Weimin; Zhao, Huanxin; Zhao, Lixia; Gan, Li-Yong; Guo, Liang-Hong
Abstract : Humic acid improves TiO2 nanocrystal stability in a facet dependent manner due to the facet-specific SRHA coordination on the TiO2 surface. Abstract : Interfacial interactions between TiO2 nanocrystals and the surrounding environmental media play a critical role in dictating their environmental behaviors. Here two specific-faceted TiO2 crystals, 101 facet and 001 facet, were adopted to investigate facet-mediated aggregation kinetics in aquatic environments. In pristine electrolyte solution (NaCl and CaCl2 ), 001 TiO2 exhibited higher stability than 101 TiO2 due to the abundant –OH groups on the 001 facet surface. The presence of Suwannee river humic acid (SRHA) significantly improved the stability of TiO2 nanocrystals in a facet dependent manner, in which 101 TiO2 exhibited a more remarkable improvement in stability than 001 TiO2 . At a high SRHA concentration (10 mg L −1 ), both faceted TiO2 displayed comparable stability. The adsorption experiments and attenuated total reflectance Fourier transformation infrared spectroscopy demonstrated that 101 TiO2 induced more pronounced adsorption of SRHA molecules than 001 TiO2, probably driven by the efficient bidentate coordination of –COO– groups in SRHA on the 101 facet. This facet-affected colloidal stability behavior would deepen our understanding on nanomaterial transport and exposure in natural waters.